Couples' psychological adjustment to twin parenthood: mode of conception (spontaneous versus assisted reproduction) and gender differences - Tendais, Iva Alexandra Barbosa (2019)
Aim: To examine whether mode of conception and gender are associated with parents’ psychological adjustment across the transition to twin parenthood. Background: There is limited knowledge on the psychological adjustment of couples to twin parenthood during pregnancy and early postpartum, especially for fathers. The available research suggests that first-time mothers of twins conceived by assisted reproduction techniques (ART) may experience lower psychosocial well-being than mothers of spontaneously conceived (SC) twins. Methods: A total of 41 couples expecting twins, 25 of whom conceived spontaneously and 16 conceived by assisted reproduction techniques, completed measures of depressive and anxiety symptoms, marital relationship, attitudes to sex, and attitudes to pregnancy and the baby. Findings: ART parents showed a decline in marital relationship quality, no changes in attitudes to pregnancy and the baby and no changes in attitudes to sex over the postpartum. In contrast, SC parents did not change their perception of the marital relationship, reported more positive attitudes to pregnancy and the baby, and more positive attitudes to sex over the postpartum. Compared with the other groups (SC mothers and fathers, ART fathers), ART mothers exhibited a higher increase in depressive and anxiety symptoms from pregnancy to postpartum and only anxiety symptoms exhibited a decline trend over the postpartum. These findings suggest that ART parents may experience more psychological difficulties during the transition to twin parenthood than SC parents. ART mothers, in particular, appear to be more at risk of high levels of postpartum depressive symptoms.